ANALYSIS OF THE DISTRIBUTION OF MERCURY POLLUTION (HG) IN RIVER WATER IN PASIE RAJA DISTRICT, SOUTH ACEH REGENCY - Darmawan Darmawan; Susy Sriwahyuni (RADJA PUBLIKA, 2022)
The method used by the Pasie Raja community in processing gold is using the amalgamation, which uses chemicals as chemicals to extract the seeds.waste mercury produced is channeled into the river near the mining site in the Sungai Pasie Raja sub-district. The purpose of this study was to analyze the distribution of mercury (Hg) in river water in Pasie Raja District, South Aceh Regency. The method used in this research is a qualitative method with a descriptive method. The results of this study indicate that the highest mercury levels in the river water of Pasie Raja District, South Aceh Regency, are found in the lower reaches of the river, reaching a value of 0.02145 mg/l and the lowest is in the middle, which is <0.0005 mg/l. The conclusion of this study is that river water in Pasie Raja District, South Aceh Regency has been polluted by mercury because the mercury levels in the river water have exceeded the normal threshold for quality standards according to the Ministerial Republic of Indonesia Number 57 of 2016 which is 0.001. It is recommended to the local government to provide direction and understanding to local gold miners about the dangers of using mercury and the negative impact on society, if used sustainably to local gold miners.